Integrated Ricefield Pond Systems: Linking Fish, Rice, Livestock and Livelihoods Khmer - Sean, Vichet; Mam, Kosal (WorldFish, 2025)
Integrated Ricefield Pond Systems bring together fish, rice farming, and livestock production within a shared landscape. This approach enhances resource efficiency, diversifies income, and strengthens resilience to climate change. By recycling nutrients and optimizing land and water use, farmers can improve productivity and food security while maintaining ecological balance. The system supports sustainable livelihoods by linking different farming components, contributing to both environmental and economic sustainability in rural communities. Training material like poster on ricefield systems are important because they provide farmers with clear, visual, and practical guidance that is easy to understand and remember. Posters can simplify complex concepts, demonstrate improved practices step-by-step, and serve as a quick reference tool in the field. They also help standardize key messages, ensuring consistent knowledge transfer across communities, and can be widely shared during trainings, meetings, or displayed in villages. By making information more accessible, posters strengthen farmer learning, encourage adoption of improved practices, and support the scaling of ricefield innovations.